Mobile health systems: a brief overview - Pattichis, Constantinos S.; Kyriacou, Efthyvoulos C.; Voskarides, Sotos (My University, 2002)
Rapid advances in information technology and telecommunications, and more specifically wireless and mobile communications, and their convergence (telematics) are leading to the emergence of a new type of information infrastructure that has the potential of supporting an array of advanced services for healthcare. The objective of this paper is to provide a snapshot of the applications of mobile technology in healthcare. A brief review of the spectrum of these applications and the potential benefits of these efforts will be presented, followed by success case studies in electronic patient record, emergency telemedicine, teleradiology, and home monitoring. It is anticipated that the progress carried out in these efforts, and the potential benefits of emerging mobile technologies will trigger the development of more applications, thus enabling the offering of a better service to the citizen.
Keywords: Global system for mobile communications; Wireless communication systems; Telecommunications; Local area networks (Computer networks)